2004
DOI: 10.1152/ajplung.00275.2003
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses to LPS in mouse lung are suppressed and reversed by neutralization of GM-CSF via repression of TLR-4

Abstract: The innate immune inflammatory response to lipopolysaccharide (LPS, an endotoxin) is essential for lung host defense against infection by gram-negative bacteria but is also implicated in the pathogenesis of some lung diseases. Studies on genetically altered mice implicate granulocyte-macrophage colony-stimulating factor (GM-CSF) in lung responses to LPS; however, the physiological effects of GM-CSF neutralization are poorly characterized. We performed detailed kinetic and dose-response analyses of the lung inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
91
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 61 publications
15
91
2
1
Order By: Relevance
“…These findings are consistent with previous findings showing an important role of GM-CSF in granuloma formation 24,40 and the importance of GM-CSF on secretion of macrophage TNFα. 10,23,36,48,49 TNFα is a critical mediator of granuloma formation in tuberculosis. 24,50,51 However, our findings in GMKO mice indicate that protection of the distal lung epithelial cells must be secured early in the course of the infection even before granuloma formation and immunological containment of virulent mycobacteria can take place locally.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous findings showing an important role of GM-CSF in granuloma formation 24,40 and the importance of GM-CSF on secretion of macrophage TNFα. 10,23,36,48,49 TNFα is a critical mediator of granuloma formation in tuberculosis. 24,50,51 However, our findings in GMKO mice indicate that protection of the distal lung epithelial cells must be secured early in the course of the infection even before granuloma formation and immunological containment of virulent mycobacteria can take place locally.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is warranted to answer this important question. Significantly, inhibition of IκBα and IKKs has been Further, Bozinovski et al showed that LPS-induced lung inflammation is ameliorated by neutralizing GM-CSF (69). Finally, elevated levels of GM-CSF, in addition to IL-6 and IL-8, were recently found in amniotic fluid in the setting of infection (70).…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Amentioning
confidence: 99%
“…The purified total RNA rep was used as a template to generate first-strand cDNA synthesis using Super Script II (Invitrogen) as described previously (Bozinovski et al, 2004). The reaction mix containing 1 mg of RNA, 250 ng of random hexamers (Promega), and 10 mM dNTP mix was diluted to 12 ml in sterile water, heated to 651C for 5 min and chilled on ice for 1 min.…”
Section: Ucp1 Ucp3 and Tnf A Measurementmentioning
confidence: 99%
“…cDNA was diluted 10-fold in sterile water and stored at À201C prior to amplification. Quantitative real-time PCR was performed as described previously (ABI PRISM 7900 HT Sequence Detection System) (Bozinovski et al, 2004) using predeveloped primers from Applied Biosystem. Briefly, gene expression was quantified by multiplexing single reaction, where our gene of interest (UCP1, UCP3, and TNF a) was standardized to control (18 s rRNA).…”
Section: Ucp1 Ucp3 and Tnf A Measurementmentioning
confidence: 99%